Association Between Physical Activity and Metabolic Syndrome among Patients in Primary Public Health Center - Maruf Agung; Ririn Puspita; Dwi Lisa Nuraini; Iche Andriyani Liberty (Majalah Kedokteran Sriwijaya, 2019)
Metabolic syndrome is a major challenge to public health throughout the world, about a quarter of the world's adults suffer from metabolic syndrome. Many studies have concluded that differences in the level of physical activity is associated with the prevalence of the metabolic syndrome. The main objective of this study was to evaluate the associated between physical activity and metabolic syndrome in 2 (two) Primary Public Health Center in Palembang City. This study was an observational analytic study with a cross-sectional design conducted on 91 subjects that met the criteria. Data on respondents' characteristics were taken from personal data interviews, physical activity was obtained by IPAQ questionnaire, lipid profile and fasting blood glucose obtained by medical records, while anthropometric and blood pressure measurement data were obtained directly through measurements. The results showed the prevalence of metabolic syndrome was 59.3% in the subject. The majority of the physical activities of the subjects were low (54.9%) followed by moderate (35.2%), and high (9.9%). Inferential analysis shows that there was a significant associated between physical activity and metabolic syndrome (p = 0.003 and POR = 1.785; CI95% = 1.19-2.66).